PENGUKURAN PERFORMASI RANTAI PASOK CANNED SARDINES PT SUMBER YALASAMUDRA: PENDEKATAN SCOR (SUPPLY CHAIN OPERATION REFERENCE) - Dora Eka Mawangi; Agus Supriono (University of Jember, 2021)
The high potential of fisheries in Banyuwangi has caused many canned sardine processing industries to be established, one of which is PT. Sumber Yalasamudra in Muncar District. In recent years the population of lemuru fish has decreased so that PT. Sumber Yalasamudra must be able to carry out good supply chain management so that the production process continues to run smoothly. This study aimed to analyze the supply chain flow and supply chain performance of PT. Sumber Yalasamudra. The research method used descriptive analysis to explain supply chain flow and SCOR analysis to measure supply chain performance of PT. Sumber Yalasamudra. The results of the analysis showed that the supply chain flow of PT. Sumber Yalasamudra are divided into 3 streams, namely (a) product flows from fishermen to final consumers (buyers), (b) financial flows flowing from downstream to upstream in cash with a period of time and (c) information flows flowing from upstream to downstream and vice versa, and supply chain performance of PT Sumber Yalasamudra based on 5 attributes of SCM (Supply Chain Management) it can be concluded that PT Sumber Yalasamudra has a good performance because it is in a superior position.